Pengaruh Store Atmosphere dan Kualitas Pelayanan Terhadap Loyalitas Konsumen Dengan Kepuasan Konsumen Sebagai Variabel Moderating - Risqy Aziz Basuki; Widiastuti Widiastuti (JOURNAL FOR BUSINESS AND ENTREPRENEURSHIP, 2021)
This study aims to empirically examine the effect of store atmosphere and service quality on consumer loyalty with customer satisfaction as a moderating variable (Survey at Caffe Pabbo & Co Jakarta). The population in this study are Caffe Pabbo & Co Jakarta customers. The characteristics in this study are Caffe Pabbo & Co Jakarta customers 2 times or more who have made a purchase transaction. The sampling technique was carried out using a non-probability sampling technique with a purposive sampling technique. Using the Marchin & Campell formula (Population unknown). This research will use Partial Least Square software (PLS). The results of this study indicate that the store atmosphere has a negative and insignificant effect on consumer loyalty, service quality has a positive and significant effect on consumer loyalty, consumer satisfaction has a positive and significant effect on consumer loyalty, consumer satisfaction has a positive and significant effect on the store atmosphere moderated by consumer loyalty, consumer satisfaction has a positive and significant effect on service quality moderated by consumer loyaltyKeywords: Store Atmosphere, Service Quality, Consumer Satisfaction, Consumer Loyalty